Detection and Absolute Quantification Porcine DNA in Sausages Using Quantitative Polymerase Chain Reaction (qPCR) Method - Syafrizayanti; S. Safni; Nurhayati (Departemen Kimia Universitas Andalas, 2022)
Identification of adulteration of processed meat products with unwanted ingredients is a crucial issue. These meat products are prone to forgery and mix with porcine. Meat source authentication is important for Muslim consumers to whom comsumption of products containing pork and its derivatives in an products is prohibited. This present study aims at development of detection and quantification method of porcine DNA (Deoxyribo Nucleic Acid) in processed meat products, sausages. Two novel primer pairs were designed specifically targeting fragment of Displacement Loop (D-Loop) and cytochrome b (cyt b) of porcine mitochondrial DNA and to generate 139 bp and 143 bp amplicons, respectively. Detection and quantification were accomplished by Quantitative Polymerase Chain Reaction (qPCR). Porcine DNA standard curves and cycle threshold were used for quantification. The detection limit of porcine DNA was as little as 0.05 pg. Of all sausages tested (n=13), four of them contained porcine DNA as much 3.1 pg; 0.160 pg; 0.294 pg; and 0.110 pg in 0.001 mg of sausages for J, G, I, and L samples respectively. The specific qPCR assay method can be used for the detection of porcine DNA in minute amounts, which can be used for the halal authentication of food and pharmaceutical products.